2015
DOI: 10.1111/jen.12286
|View full text |Cite
|
Sign up to set email alerts
|

A real‐time PCR toolbox for accurate identification of invasive fruit fly species

Abstract: Significant plant pests such as fruit flies that travel with fresh produce between countries as eggs or larvae pose a great economic threat to the agriculture and fruit industry worldwide. Time‐limited and expensive quarantine decisions require accurate identification of such pests. Immature stages are often impossible to identify, making them a serious concern for biosecurity agencies. Use of COI barcoding PCR, often the only molecular identification resource, is time‐consuming. We assess the suitability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…The annealing temperature of 65°C was selected for the real‐time PCR assays for B. tryoni complex due to the cross‐reaction with the closely related species (Dhami et al, ); however, at this temperature (65°C), lower amplification efficiency was observed for the real‐time PCR assays of Z. cucumis or B. jarvisi in the current study. On the other hand, the assays for Z. cucumis or B. jarvisi have the possibilities to be used as multiplex with the assays targeting other Tephritidae interceptions, such as B. dorsalis complex, Dirioxa pornia and Ceratitis capitata (Dhami et al, ). Further validations are required prior to application of these as multiplex assays in diagnostics.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The annealing temperature of 65°C was selected for the real‐time PCR assays for B. tryoni complex due to the cross‐reaction with the closely related species (Dhami et al, ); however, at this temperature (65°C), lower amplification efficiency was observed for the real‐time PCR assays of Z. cucumis or B. jarvisi in the current study. On the other hand, the assays for Z. cucumis or B. jarvisi have the possibilities to be used as multiplex with the assays targeting other Tephritidae interceptions, such as B. dorsalis complex, Dirioxa pornia and Ceratitis capitata (Dhami et al, ). Further validations are required prior to application of these as multiplex assays in diagnostics.…”
Section: Discussionmentioning
confidence: 86%
“…The real‐time PCR assays developed in this study have been validated in one tube as duplex assay if the intercepted Tephritidae samples are suspected to be either Z. cucumis or B. jarvisi . For the current assay formats, it is not possible to multiplex the real‐time PCR assays for Z. cucumis or B. jarvisi in this study with the real‐time PCR assay for B. tryoni complex (Dhami et al, ) due to the difference in the annealing temperatures. The annealing temperature of 65°C was selected for the real‐time PCR assays for B. tryoni complex due to the cross‐reaction with the closely related species (Dhami et al, ); however, at this temperature (65°C), lower amplification efficiency was observed for the real‐time PCR assays of Z. cucumis or B. jarvisi in the current study.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations